Aplikasi Pembelajaran Pada Kelas VI SD Menggunakan Metode Linear Congruent Method - Iwan Noor Saputra; Rina Candra Noor Santi (Elkom: Jurnal Elektronika dan Komputer, 2022)
At this time the learning process is still partially carried out online (in the network) considering the positive cases of Covid-19 that still exist in the Semarang City area. The implementation of online learning is not without problems, even in several countries, especially Indonesia, it is reported that countries that adopt online learning on average are actually much smaller than expected. The implementation of online learning makes students less understanding of the learning materials provided and students' low interest in learning during the pandemic. This study aims to create a learning application for grade VI elementary school students that contains learning materials, practice questions that are randomized using LCM and facilitate the results of the assessment of the questions. From the results of LCM randomization, each student did not get the same or twin questions. From the test of 3 students, it was found that the questions that appeared in the same order were question number 6, while the questions that appeared in a different order were questions number 2, 3, 4, 5, 7, 8, 9, 10